Serological survey for the detection of leptospiral antibodies in dogs in Thessaloniki area - ΜΑΖΑΡΑΚΗΣ, Κ.; ΣΑΡΡΗΣ, Κ.; ΔΑΜΠΑΑΗΣ, Θ.; ΠΑΠΑΔΟΠΟΥΛΟΣ, Ο. (Journal of the Hellenic Veterinary Medical Society, 2019)
Sera of 151 dogs were examined by the agglutination-lysis test for leptospiral antibodies, using 18 leptospiral antigens. Among them 19 were from dogs clinically suspect for leptospirosis. In the screening test, in the 1:30 dilution all were positive, while 3 had a titre of 1:100, 6 1:200 and 2 1:400. After treatment with 2-ME, 8 were positive in the 1:100 dilution to one serotype (3 to L. bratislava, 2 to L. icterohaemorrhagiae frysawa, 1 to L. canicola, 1 to L. Sejroe M 84 and one to L. grippotyphosa). Of the 132 healthy dogs 67 serums were positive in the 1:30 dilution, while 12 had a titre of 1:100, 14 of 1:200 and 4 of 1:400. After treatment with 2ME, 14 were found positive in the 1- :100 dilution to one serotype. (6 to L. canicola, 5 to L. icterohaemorrhagiae frysawa, 1 to L. po mona, 1 to L. panama and 1 to L. grippotyphosa).